#TITLE_ALTERNATIVE# - Nugroho - Nim: 15113070, Cahyo
Tidal design is vertical references model describing various tidal levels with respest to a specific vertical reference plane (mostly local reference plane). Nowadays, tidal design information is highly available as secondary data. When combined with other parameters such as geoid undulation and sea surface topography, tidal design with respect to global ellipsoid can be generated. Derived from secondary data, the model would contain uncertainty and needs to be assessed. The uncertainty is calculated by means of statistical operation and error propagation through many data sample points. The assessment is done by comparing the results of error propagation with some specific standard. For generalization of the whole Southwest of Java Sea, the result is interpolated with spatial interpolation method. The generated tidal design model also has to comply with practical data from field. Based on the applied method, two tidal design is successfully generated namely LAT and MSS. LAT tidal design complies well with the Order 1 of IHO S-44 and predicted to able to comply with Order 2 as well. MSS tidal design is able to comply with the practical data in fractions up to decimeter to centimeter.